Regulating religion: state governance of religious institutions in South Africa - Van Coller, Helena (ICLARS series on law and religion, 2019)
Cover; Half Title; Series Page; Title Page; Copyright Page; Table of Contents; Preface; List of cases; PART 1; 1. Introduction and Background; Church and state relationship in South Africa; A new approach -- the constitutionally protected right to freedom of religion; Conclusion; Bibliography; 2. The nature and legal status of religious institutions; Introduction; The nature and meaning of 'religious organisation'; Legal status; Conclusion; Bibliography; 3. Collective religious rights and religious autonomy; Introduction; Collective religious rights; Religious autonomy; Conclusion